Montanism and Its Trinitarian Significance - Pelikan, Jaroslav (Church history, 1956)
It has become almost a commonplace of both historical and systematic theology to interpret the doctrine of the Trinity as an elaboration of the christological faith and formulations of the early church. That is true of such radically divergent interpreters of that doctrine's origin as Adolf Harnack and G. L. Prestige. Both these scholars agree in seeing the trinitarian dogma as a response to the question whether, in Harnack's words, “the divine that has appeared on earth and reunited men with God is identical with that divine which created heaven and earth, or whether it is a demigod.” Or, as Prestige elaborates the thesis: “If the godhead was not unitary, it was as simple to conceive of three Persons as of two; hence the deity of Christ carried the weight of trinitarian controversies without any necessity for extending the range of dispute, and as a matter of history, the settlement of the problems connected with the Father and the Son was found to lead to an immediate solution of the whole trinitarian difficulty.”